APPLICATION OF RESITATION LEARNING METHOD IN IPS SUBJECT IN CLASS VIII SMP O. MANGUNHARJO - Ningrum, Fitriyan Della Widya; Sustianingsih, Ira Miyarni; Isbandiyah, Isbandiyah (JURNAL EDUSCIENCE, 2024)
This study aims to determine whether the application of the Resitation learning method in social studies subjects of class VIII students of SMP Negeri O. Mangunharjo significantly completed. The method used in this research is quantitative by using a pseudo-experimental approach. The population of this study is the entire class VIII SMP Negeri O. Mangunharjo which amounted to 109 students and the sample taken in this study is class VIII D which amounted to 26 students. The sample was taken by Simple Random Sampling. The conclusion of this study is whether the social studies learning outcomes of students in grade VIII SMP Negeri O. Mangunharjo after the application of the Resitation learning method is significantly complete. This can be seen from the results of the analysis with the t-test obtained tcount> ttable (6.20) > (1.708) this means Ho is rejected and Ha is accepted.